2015
DOI: 10.1002/cld.488
|View full text |Cite
|
Sign up to set email alerts
|

Amebic liver abscess

Abstract: http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046-2484/homepage/6-2-reading-anesi.htm a video presentation of this article https://wileyhealthlearning.com/Activity/3548216/Activity.aspx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
(34 reference statements)
0
23
0
1
Order By: Relevance
“…However, the real number of Entamoeba infected subjects who develop AHA, is unknown. AHA has been reported following travels to endemic areas for very brief periods (4 days) (Anesi & Gluckman, 2015;Lachish et al, 2016).…”
Section: Amebian Hepatic Abscessmentioning
confidence: 99%
“…However, the real number of Entamoeba infected subjects who develop AHA, is unknown. AHA has been reported following travels to endemic areas for very brief periods (4 days) (Anesi & Gluckman, 2015;Lachish et al, 2016).…”
Section: Amebian Hepatic Abscessmentioning
confidence: 99%
“…Aspirated material from an amebic liver abscess contains acellular, proteinaceous debris with necrotic hepatocytes that form a brown fluid referred to as “anchovy paste” [ 7 ]. Trophozoites can also be seen in a minority (<20%) of aspirates [ 8 ]. This is in contrast to aspirates from pyogenic liver abscesses which consist of purulent material with bacteria and neutrophils that are readily apparent by Gram stain.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that Mexico is one of the countries with the highest rate of E. histolytica infection [3,7,[18][19]. This was mainly based on a national survey carried out in 1994 in a representative sample of the Mexican population, which found a seroprevalence of 8.41% for E. histolytica using indirect hemagglutination [8].…”
Section: Discussionmentioning
confidence: 99%